Moving beyond charity to philanthropy?: The case of charitable giving in Thailand - Phaholyothin, Natalie (Österreichische Zeitschrift für Südostasienwissenschaften, 2017)
This paper outlines the characteristics of the philanthropic sector in Thailand today. It first describes the local concept of giving, which is intricately linked to Theravada Buddhism. Then, the paper provides examples of traditional forms of philanthropic institutions that are more closely associated with charity than philanthropy, followed by examples of innovative forms of philanthropic efforts. Given the trajectory of economic development in Thailand, opportunities to engage broader public interest in philanthropy exist and in order to do so, there is need for the sector in general to build stronger evidence of how public giving is translated into social impact. The main challenge to the Thai philanthropic sector is the limited attention to accountability and transparency, as philanthropic entities generally have not developed robust monitoring and evaluation frameworks that target outcomes. This can be turned into an opportunity to address the general lack of focus on strategy development, weak monitoring systems, and a limited reporting of outcomes. (ASEAS/GIGA)